Comparison of Survival Rates of Stainless-Steel Crowns Placed with and without Pulpotomy: A Two-Year Retrospective Study - Fatmah N. AlMotawah; Sharat Chandra Pani; Tala AlKharashi; Saleh AlKhalaf; Mohammed AlKhathlan; Fahad AlSultan; Ahmad AlMughirah (Hindawi Limited, 2020)
Aim. This study aimed to retrospectively compare the survival outcomes over two years between teeth with proximal dental caries that were restored with stainless-steel crowns to those that were pulpotomized and then restored with a stainless-steel crown in patients who were rehabilitated under general anesthesia. Participants and Methods. The records of 131 patients aged between two to six years who had stainless-steel crowns placed under general anesthesia and had two-year follow-up were screened. 340 teeth with moderate proximal caries on the radiograph (D2) were included in the study. Of these, 164 teeth were treated with a pulpotomy and stainless-steel crown, while 176 teeth were crowned without a pulpotomy. The type of each tooth was compared using the Chi-squared test and Kaplan-Meier survival analysis, and curves were plotted based on the two-year outcomes. Results. Treatment: the sample comprised 59 males (mean age 4.73 years, SD ± 1.4 years) and 72 females (mean age 5.2 years, SD ± 2.0 years). The Kaplan-Meier regression model showed no significant difference in survival outcomes between teeth that had been pulpotomized and those that had not (p = 0.283). Conclusion. Within the limitations of the current study, we can conclude that performing a pulpotomy does not influence the survival outcome of mild/moderate proximal caries restored with stainless-steel crowns under general anesthesia.